Subjective assessment of the impact of COVID-19 on life aspects of healthcare workers in the emergency internal medicine clinic – case study - Kranjčević-Ščurić, Mihaela; Ščurić, Ivica; Filej, Bojana (Nursing in the 21st Century, 2021)
SUBJECTIVE ASSESSMENT OF THE IMPACT OF COVID-19 ON LIFE ASPECTS OF HEALTHCARE WORKERS IN THE EMERGENCY INTERNAL MEDICINE CLINIC – CASE STUDY Aim. An aim was to study the impacts of COVID-19 on the lives of healthcare workers involved in treatment, care and diagnosis of positive patients. Material and methods. The research was based on a qualitative research approach – a case study. Semi-structured interviews were performed with three healthcare workers from the emergency internal medicine clinic. Results. The data obtained from the research can be summarized in 3 categories: the impact of COVID-19 on professional and private life and the impact of COVID-19 on personality and internal changes. Within the categories, another 14 subcategories were structured. The COVID-19 pandemic negatively affects all aspects of the lives of healthcare workers and generates negative emotions. The most commonly expressed emotion is fear; where fear for others, for existence and the future prevails. The epidemic also refl ected on the inability to meet the basic human needs of the respondents. Conclusions. To reduce the negative impact of pandemic on work, additional research is needed to assess its influence on employees. The research suggests the inclusion of psychological support as well as more extensive education for employees to reduce the possibility of burnout in the workplace, anxiety, depression and worries about existence.